G44(P) A quality improvement project for safe and standardised central line insertion on PICU. (May 2019) - Thompson, A; Webster, A; Zizkova, E; Burmester, M
Abstract : Aims: The 2015 NHS England document 'National Safety Standards for Invasive Procedures' (NatSSIPs), outlines a series of standards to enable safe and standardised care for patients undergoing invasive procedures in hospital. The NatSSIPs can be modified locally to produce 'Local Safety Standards for Invasive Procedures' (LocSSIPs). This project looked at the LocSSIP entitled 'Paediatric Vascular Access Form', designed for assisting with safe insertion and documentation of central lines on PICU. The aims were to audit the use of the form, develop strategies to improve its use and then re-audit. Methods: A list of all PICU inpatients during October 2017 was generated retrospectively from the patient database. All clinical notes were reviewed. Patients who had a central line inserted on PICU were included. The notes were reviewed for use of the 'Paediatric Vascular Access Form' for each line inserted, and if used, whether it was completed in full. Following the initial audit, a series of improvement strategies were implemented: Education and training on the LocSSIP during new doctors' induction Education and training on the LocSSIP to current medical and nursing teams on PICU Development of a reminder sticker attached to all central line packs Development of posters with instructions on how to complete the form circulated around PICU Following the improvement strategies, a re-audit was undertaken during the month of April 2018. Results: Conclusions: Following the intervention strategies the use of the LocSSIP the 'Paediatric Vascular Access Form' was much improved from 24% to 89% (table 1 ). Education and training sessions, reminder posters and stickers on central line packs can therefore be assumed to have improved the use of the form. Completion of all sections of the form was also improved, from 25% to 63%. However there is room for further improvement and consideration of appointing a 'LocSSIP Champion' has been suggested to help facilitate this.